How to alleviate cardiac injury from electric shocks at the cellular level - Sowa, Pamela W.; Kiełbik, Aleksander S.; Pakhomov, Andrei G.; Gudvangen, Emily; Mangalanathan, Uma; Adams, Volker; Pakhomova, Olga N. (Frontiers in Cardiovascular Medicine, 2022)
Electric shocks, the only effective therapy for ventricular fibrillation, also electroporate cardiac cells and contribute to the high-mortality post-cardiac arrest syndrome. Copolymers such as Poloxamer 188 (P188) are known to preserve the membrane integrity and viability of electroporated cells, but their utility against cardiac injury from cardiopulmonary resuscitation (CPR) remains to be established. We studied the time course of cell killing, mechanisms of cell death, and protection with P188 in AC16 human cardiomyocytes exposed to micro- or nanosecond pulsed electric field (μsPEF and nsPEF) shocks. A 3D printer was customized with an electrode holder to precisely position electrodes orthogonal to a cell monolayer in a nanofiber multiwell plate. Trains of nsPEF shocks (200, 300-ns pulses at 1.74 kV) or μsPEF shocks (20, 100-μs pulses at 300 V) produced a non-uniform electric field enabling efficient measurements of the lethal effect in a wide range of the electric field strength. Cell viability and caspase 3/7 expression were measured by fluorescent microscopy 2–24 h after the treatment. nsPEF shocks caused little or no caspase 3/7 activation; most of the lethally injured cells were permeable to propidium dye already at 2 h after the exposure. In contrast, μsPEF shocks caused strong activation of caspase 3/7 at 2 h and the number of dead cells grew up to 24 h, indicating the prevalence of the apoptotic death pathway. P188 at 0.2–1% reduced cell death, suggesting its potential utility in vivo to alleviate electric injury from defibrillation.